Pengaruh Environmental Disclosure, Environmental Cost, dan Greenwashing Terhadap Kinerja Keuangan Perusahaan Pertambangan - Rahmat Fauzan; Hendro Lukman (Jurnal Sosial Teknologi, 2026)
This study is motivated by the increasing demand for environmental transparency and sustainability in the mining sector, which has significant ecological impacts, as well as the inconsistent findings regarding the effects of environmental disclosure, environmental cost, and greenwashing on corporate financial performance. The objective of this study is to analyze the influence of these three variables on the financial performance of mining companies listed on the Indonesia Stock Exchange during the 2021–2023 period. This research employs a quantitative approach using panel data from 17 companies over three years, resulting in 51 observations. Data analysis was conducted using panel regression with the Random Effect Model supported by EViews 13, along with descriptive statistics, classical assumption tests, partial and simultaneous tests, and coefficient of determination analysis. The results indicate that environmental disclosure has a negative but insignificant effect on financial performance, environmental cost has a positive but insignificant effect, and greenwashing also shows a positive but insignificant relationship. Simultaneously, the three variables do not significantly affect financial performance. The low Adjusted R-squared suggests that environmental factors are not yet the primary determinants of financial performance in the mining sector. The study concludes that economic fundamentals remain more dominant than environmental factors in influencing corporate financial performance in Indonesia.